2011
DOI: 10.1589/jpts.23.543
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Symmetrical Self-performed Facial Muscle Exercises on the Neuromuscular Facilitation of Patients with Facial Palsy

Abstract: Abstract.[Purpose] The present study was designed to evaluate the effect of symmetric self-performed facial muscle exercises on the facial muscle function of patients with facial palsy.[Subjects] The subjects were 26 persons (men=12, women=14) who suffered from facial palsy and were treated by western-oriental medical treatment. [Methods] We educated patients to conduct symmetric self-performed facial muscle exercises three times per day for four weeks by themselves to facilitate neuromuscular function. We ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Stroke is a leading cause of neurological disability among adults and often leads to functional deficits in motor control4, 5, 11, 12 ) . Stroke involves muscle weakness, spasms, disturbed muscle timing, and a reduced ability to selectively activate muscles5, 6, 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a leading cause of neurological disability among adults and often leads to functional deficits in motor control4, 5, 11, 12 ) . Stroke involves muscle weakness, spasms, disturbed muscle timing, and a reduced ability to selectively activate muscles5, 6, 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…of subjects = 354); one quasi-experimental study ( n = 16 patients) 48 ; two pilot studies ( n = 37 patients) 49 , 50 ;and nine non-experimental observational studies ( n = 447 patients). Observational studies varied in their design: three were cohort studies ( n = 169 patients) 51 – 53 ; two were retrospective studies ( n = 101 patients) 54 , 55 ; three used group comparisons ( n = 164 patients) 56 58 ; and one a small clinical study of 13 patients. 59 In total, the research studies identified reported the impact of physical therapy in a total 854 participants (age range 12–80 years old).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased muscle activity due to a decrease of muscle loading, a lengthy period of bed rest, malnutrition, or central nervous injury such as stroke and spinal cord injury, triggers signaling pathways to induce skeletal muscle weakness and atrophy 14 , 15 , 16 , 17 , 18 ) . Initial muscle atrophy in rehabilitative areas is especially rapid, with up to one-half of the final extent of atrophy occurring within the first week of immobilization, but the severity of muscle atrophy increases for several weeks after the application of a cast 19 , 20 ) .…”
Section: Discussionmentioning
confidence: 99%